Analysis of the Need for Nurse Competency Training at Ahmad Yani Islamic Hospital Surabaya - Muhadi, Muhadi; Efendi, Ferry (Jurusan Keperawatan FIKES UNSOED, 2020)
AbstrackIntroduction: Minimum service standards field of administration and management about employee training require at least 20 hours per year. The aims of this study was to analyze the training needs of nurses at the Ahmad Yani Islamic hospital in Surabaya. In addition, this study explain the organizational analysis, conduct operational analysis, explain individual analysis nurse staff and prioritize nurse training needs in Ahmad Yani Islamic Hospital Surabaya. Method: This research is a observational description. The number of respondents about 55 nurses participating the study. Results: Based on the aspect of quantity of work, the workload of nurses is classified as high by 49.1%. Most have applied a high quantity of work aspects as much as 78.1%. In the aspect of quality of work, most nurses have performed high tasks. Conclusion: Analysis of organizations related to organizational climate at Ahmad Yani Islamic hospital in general was described by nurses in good condition. There are a number of things that need to be considered, namely guaranteed nurse self development through Training, work protection for nurses, nurse remuneration needs to be improved. Operational analysis related to the general competence of nurses in the nurse law is quite capable and most nurses have already taken action. Operational analysis relating to the priority of nurses' training needs is a main priority.Â Keywords: Operational Analysis; Individual Analysis; Nurse Training Priority.